International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2535935
|View full text |Cite
|
Sign up to set email alerts
|

ESAs ScyLight Programme: activities and status of the high throughput optical network "HydRON"

Abstract: ESA's Telecommunications and Integrated Applications Directorate (TIA) runs a dedicated programmatic framework to Optical Communication Technologies, called ARTES ScyLight (SeCure and Laser communication Technology, pronounced "skylight"). ScyLight supports the development and deployment of innovative optical technologies for satellite communication as well as assisting industry to develop new market opportunities for optical communication technologies. The ScyLight programme focuses the efforts of European an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The latter apparently provide the highest achieved to date rate at the level of several Gbit/s over distances of the order of 10 4 km [111,112]. It is reasonable to expect that the ongoing studies of advanced optical communication systems would demonstrate the data rate of the order of terabit per second [113] in the coming decade. Depending on the overall THEZA configuration, the data transport system should provide only inter-satellite link (the case of Space-only baselines) with in-orbit correlation, or enable data down-link if the system involves both space-borne and Earth-based telescopes.…”
Section: Data Transportmentioning
confidence: 94%
“…The latter apparently provide the highest achieved to date rate at the level of several Gbit/s over distances of the order of 10 4 km [111,112]. It is reasonable to expect that the ongoing studies of advanced optical communication systems would demonstrate the data rate of the order of terabit per second [113] in the coming decade. Depending on the overall THEZA configuration, the data transport system should provide only inter-satellite link (the case of Space-only baselines) with in-orbit correlation, or enable data down-link if the system involves both space-borne and Earth-based telescopes.…”
Section: Data Transportmentioning
confidence: 94%
“…In another use case for OWSNs, the European Space Agency's High thRoughput Optical Network (HydRON) project is targeting a "Fiber in the Sky" network in space [18]. The goal of this project is to enable an all-optical transport network in space.…”
Section: Motivationmentioning
confidence: 99%
“…Substituting values of different distances in (14), we get (17). Finally, the crossover function for this scenario can be calculated as in (18). Substituting 𝑟 𝑔𝑠 in (18), we get (19).…”
Section: B Scenariomentioning
confidence: 99%
“…It was shown that the crossover distance depended on the refractive index of the optical fiber in the optical fiber terrestrial network and the altitude of satellites and the end-to-end propagation distance in the FSOSN. A TL with a nearby crossing OP neighbor was considered in [25] while studying latency of a satellite network, and TLs were also considered in [13] and [29] while conducting comparison of an optical wireless satellite network Objective Deliver broadband Internet to rural and remote areas [3], [5], [19] Deliver an all-optical transport network in space [20]- [22] Timeline and an optical fiber terrestrial network in terms of latency. Yet no studies exist that examine an NG-FSOSN versus an NNG-FSOSN to investigate the impact of TLs on network latency of these FSOSNs.…”
Section: Motivation and Related Workmentioning
confidence: 99%